Development of nucleic acid-based RAA test strip assay for the rapid detection of foot-and-mouth disease virus - Chen, Wenxian; Niu, Xinni; Zeng, Weijun; Fang, Yiqi; Zhu, Zixiang; Yi, Lin; Zhao, Mingqiu; Ding, Hongxing; Fan, Shuangqi; Li, Zhaoyao; Chen, Jinding (Frontiers in Veterinary Science, 2025)
Foot-and-mouth disease virus (FMDV) causes blister-like lesions in animals, leading to significant economic losses in animal husbandry. Accurate and rapid detection of FMD is crucial for effective prevention and control. The recombinase-aided amplification (RAA) technique enables rapid amplification of target fragments under isothermal conditions. In this study, based on the conserved sequence of the FMDV 3D gene, optimal RAA primers and probes were designed and screened, and a simple, rapid, and visual FMDV nucleic acid RAA test strip was developed. The optimum reaction conditions of the assay were determined to be 32°C for 30 min. The specificity, sensitivity, and repeatability of the FMDV nucleic acid RAA test strip were evaluated. The results demonstrated that the FMDV nucleic acid RAA test strip specifically reacted with FMDV nucleic acid and exhibited no cross-reactivity with other viruses. The lowest detection limits for recombinant plasmids and virus titer were 10 copies/μL and 100 TCID50/mL, respectively. In addition, all 17 positive samples and 21 negative samples were accurately identified using the FMDV nucleic acid RAA test strip, resulting in a 100% positive detection rate. In conclusion, the FMDV nucleic acid RAA test strip developed in this study—characterized by high specificity, efficiency, and sensitivity—offers a robust technical platform for the prevention and control of FMD.